Analisis Kandungan Nutrisi Lamtoro Mineral Blok (LMB) Sebagai Pakan Tambahan pada Ternak Ruminansia - Yomi Daskunda; Godlief Joseph; Insun Sangaji (JURNAL PERTANIAN KEPULAUAN, 2020)
The study aims to determine the nutritional content of Lamtoro minerals block (LMB). This research was conducted in the Laboratory of beef cattle, and the Department of Animal Husbandry, Agriculture Faculty at the Pattimura University, which took place from April to June 2019. Proximate analysis was carried out at the Laboratory of Biological Resources Research Center and Biotechnology, IPB University. Variables observed in this study were crude protein, crude fiber, crude fat moisture content, and ash content of Lamtoro minerals block (LMB). Based on the result of this study, it can be concluded that the Lamtoro minerals block has good nutritional content, namely crude protein is 28,84% and crude fiber is 5,4% so that it can be used as additional feed in the ruminants farming business.